Aligning Islamic inputs into the medical imaging practice: a conceptual approach using professional guidelines - Zainuddin, Zainul Ibrahim (IIUM Press, 2015)
Being relatively new in medicine, Medical Imaging (Radiography) practice has been dictated by the Western Worldview. Various Professional guidelines are available to guide Medical Imaging professionals in terms of the professional and ethical aspects in the field. They are known by various terminologies that include Code of Practice, Code of Ethics and Standards of Best Practice. Formulated by those who championed the concept of secularisation, these guidelines are devoid of any references to the Divine Creator or spiritual associations. Subconsciously, Muslim practitioners could have embraced this systematic indoctrination of Western values and practices. The effective secularisation of spiritual values and practices could result in distancing these individuals from the principles and objectives of the Shari’ah and to those ideals that Islam champions. Attempts must be made to guide the Muslim practitioners to appreciate the Islamic beliefs, values and practices into the realm of the vocation. This paper examines selected professional guidelines to identify some of the common professional and ethical themes that they represent. The paper begins with the discussion on profession, professional, professionalism and ethics. This is followed by a brief history of Islamic professionalism and ethics. Seven common themes or constructs were discussed alongside relevant Islamic inputs, with the intention of reinforcing and enhancing further the spiritual mindedness and practice of the Muslim practitioners. The Islamic inputs include Qur’aanic verses, Hadith and the Maqasid and Qawa’id Al-Shariah. Three important Islamic concerns that were not outlined in the guidelines are discussed. Ultimately, the integration effort could become a catalyst to the formulation of the Code of Professional Practice for Muslim Medical Imaging Practitioners.